Developing a Reference Database for Typical Body and Organ Growth of the Artificially Reared Pig as a Biomedical Research Model - Vu, Vinh H.; Donovan, Sharon M.; Brink, Lauren R.; Li, Qian; Gross, Gabriele; Dilger, Ryan N.; Fleming, Stephen A. (Frontiers in Pediatrics, 2021)
Objectives: The pig is a common model utilized to support substantiation of novel bioactive components in infant formula. However, reference ranges for outcomes to determine safety are unclear. Our objective was to use historical data to objectively define typical body and organ growth metrics of the domesticated pig in research. Methods: Twenty-two studies were compiled to assess typical growth of body and organ weights in young pigs. Metadata were organized to include milk replacer sources, bioactive components, sex, breed, source of herd, feeding regimen, and rearing environment. A combination of statistical models including simple linear regression and linear mixed effect models were used to assess typical growth patterns. Results: Over 18,000 data points from 786 animals were available. In general, minimal differences in the growth of pigs who were male and female, artificially- or sow-reared, or fed ad libitum- or by scheduled-feeding, were observed in the first 30 days of life (P > 0.05). A weight-for-age chart from reference pigs was developed to compare body weights of pigs demonstrating accelerated, typical, reduced, and failure to thrive to illustrate effects of e.g., dietary interventions. Distributions of relative brain, liver, and intestine weights (as % of total body weight) were similar between rearing environments and sexes. An alternative bivariate level approach was utilized for the analysis of organ weights. This approach revealed significant biologically-relevant insights into how deficient diets can affect organ weight that a univariate level assessment of weight distribution was unable to detect. Conclusions: Ultimately, these data can be used to better interpret whether bioactive ingredients tested in the pig model affect growth and development within typical reference values for pigs in the first 30 days of life.